Road Rage Behaviour In Movie Unhinged Directed By Derrick Borte Through Psychoanalytic Approaches - Destrianaputri Ramadita (EDUJ : English Education Journal, 2023)
Road rage is a phenomenon that involves the connection between human anger and driving performance. This study aims to discover about how road rage is being portrayed in movie Unhinged and to know the interconnection between characters based on their background and motives. This research uses the psychoanalysis theory of Freud in "Unhinged" to discover the characters’ backgrounds and motives. The research adopts a qualitative approach. Through non-numeric data analysis, the study provides an overview of road rage, including its causes and severe consequences depicted in the movie. The examination of various scenes in the movie reveals similarities in the motives of the characters, despite their distinct backgrounds and personalities, which are both explicitly and implicitly explained. By analyzing the backgrounds of the characters, an interconnected negative influence between them is inferred. Ultimately, this study concludes that Unhinged prominently highlights road rage as its central theme, and through a deep analysis of character backgrounds, it unveils the overwhelming burden of thoughts experienced by both individuals, leading to heightened sensitivity on that particular day.